2018
DOI: 10.5455/medarh.2018.72.227-229
|View full text |Cite
|
Sign up to set email alerts
|

Congenital True Aneurysm of the Right Superficial Temporal Artery

Abstract: Introduction:Superficial temporal artery aneurysms (STAAs) occur in 1% of arterial aneurysms; mostly (95%) are pseudoaneurysms following trauma; true aneurysms are rare (5%); forty-five cases are reported.Aim:To report a rare case of a congenital STAAA.Case Report:A67-year-old patient recalled the existence of a true-histologically evidenced- aneurysm of the right superficial temporal artery since his childhood denying any head injury; it was resected through a horizontal skin incisure. Brain arteries’ magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We included 45 studies in the present systematic review after full-text screening [Figure 3]. [1,5,[7][8][9][10][11][12][13][14]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,[38][39][40][41][42][43][44][45][46][47]49,55,57,58,[61][62][63] According to the systematic review, 63 cases, including the present case, were identified after Brown first reported pathologically confirmed nontraumatic true STAA in 1942. All of the data acquired following the standardized form are shown in Supplementary Tables 1 and 2.…”
Section: Search Resultsmentioning
confidence: 99%
“…We included 45 studies in the present systematic review after full-text screening [Figure 3]. [1,5,[7][8][9][10][11][12][13][14]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,[38][39][40][41][42][43][44][45][46][47]49,55,57,58,[61][62][63] According to the systematic review, 63 cases, including the present case, were identified after Brown first reported pathologically confirmed nontraumatic true STAA in 1942. All of the data acquired following the standardized form are shown in Supplementary Tables 1 and 2.…”
Section: Search Resultsmentioning
confidence: 99%
“…True superficial temporal artery aneurysm (STAA) is rare, with pseudo-aneurysms being more common and are thought to be due to the artery-undergoing shear and crush as it passes over the bony ridge from where the temporalis muscle takes origin [2]. The etiology of true STAA varies from being congenital to atherosclerosis, degenerative, connective tissue disorder and infective pathology.…”
Section: Discussionmentioning
confidence: 99%